Z działalności Nicolae Titulescu w Lidze Narodów (1920-1936) - Dubicki, Andrzej (Acta Universitatis Lodziensis. Folia Historica, 2005)
Nicolae Titulescu started his career in the League of Nations on January 10th, 1920, signing on behalf of Romania the treaty which had created this international organisation. This great Romanian diplomat represented his country in the League from 1920 till 1932 with a short break in 1927-1928 period, when he held the Romania’s Foreign Affairs Office for the first time. Titulescu saw in the League a powerful force which could maintain peace in the world. The Romanian diplomat was involved in many actions undertaken by this organisation: he helped create the „Geneva Protocol”, played a vital role in the preparation of the „Litvinoff Protocol”, and was also involved in proceedings of the Geneva Disarmament Conference. As a head of the Romanian delegation in Geneva he was twice elected president of the annual meeting of the League of Nations Assembly in 1930 and 1931. He continued his Geneva activities even when he was Minister of Foreign Affairs of Romania from 1932 till 1936. During this period he was active in attempts of putting an end to the Abissynian War in 1935/36 and at the Montreux Conference, when a matter of the Black Sea straits was disputed.